A PROSPECTIVE STUDY ON TESTICULAR MAPPING AND ITS CO-RELATION WITH SERUM HORMONAL LEVELS. - Agarwal, Piyush; Panda, Kshirabdhi Tanaya; Neniwal, Vishal; Rulaniya, Suresh Kumar; D.Hota (Student’s Journal of Health Research Africa, 2024)
Background Azoospermia, the complete absence of sperm in the ejaculate, is a major cause of male infertility, affecting 1% of men globally. It is categorized into obstructive azoospermia (OA) and non-obstructive azoospermia (NOA), with NOA being more prevalent and presenting challenges for sperm retrieval. Despite advances in techniques like intracytoplasmic sperm injection (ICSI), reliable markers for successful sperm retrieval in NOA remain unclear. Aims This study aims to evaluate histopathological abnormalities in azoospermic males and assess the efficacy of testicular mapping for sperm retrieval. It also focuses on the diagnostic value of serum inhibin B and other hormones in distinguishing OA from NOA. Methods This was a prospective study involving 54 male patients diagnosed with azoospermia, assessed through a compound testicular mapping procedure with 14 microbiomes. Hormonal assessments such as follicular stimulating hormone (FSH), luteinizing hormone (LH), testosterone, and inhibin B were conducted before and after the biopsy. Histopathological analysis was focused on confirming azoospermia, differentiating OA from NOA, and identifying focal spermatogenesis. Statistical analysis correlates hormone levels with biopsy findings to evaluate diagnostic outcomes. Results The study analyzed 54 cases of azoospermia in men aged 20-39 years, with non-obstructive azoospermia (NOA) being more prevalent (74.1%) than Obstructive Azoospermia (OA) (25.9%). NOA cases were further classified into hypospermatogenesis, maturation arrest, and Sertoli cell-only syndrome. Hormonal analysis revealed significant differences in serum LH, FSH, testosterone, and inhibin B levels across azoospermia subtypes, with serum inhibin B showing the highest sensitivity and specificity for differentiating OA and NOA. The findings underscore hormonal variability and the potential of inhibin B as a clinical marker for azoospermia classification. Conclusion The study highlights significant hormonal differences between obstructive and nonobstructive azoospermia subtypes, with serum Inhibin B emerging as the most reliable marker for differentiation.